The Effect of Entrepreneurial Competencies and Networks Towards the Success of Small Sized ConstructionFirm in Malaysia - Nazaruddin, Ishak (2015)
The construction industry plays an important role in the economic growth and in the long-term national development. The industry acts as a catalyst to stimulate the growth of economy in generating wealth and development of social, infrastructures and buildings. Government tends to use their investments in construction to introduce changes in the national economies. Small sized contractors that are categorized as G1 to G3 continue to be the backbone of the Malaysian construction industry that represented 87.1 percent of the total establishments in that sector. Some studies have shown that the failure rate and bankruptcies among the construction firms are high. One of the critical issues facing the construction industry in Mala'sia is to ensure that the industry can attain and able to sustain the anticipated growth. This research attempts to empirically examine and evaluate the significance of the entrepreneurial competencies and entrepreneurial networks on entrepreneurial success of small size contractors in Malaysia. Entrepreneurial competencies are defined as the total ability of the entrepreneur to perform tasks successfully. On the same note, for the purpose of starting and sustaining the business venture, entrepreneur further need to obtain most resources from outside or his/her external environment through the entrepreneur's networks. Small firms need supports and resources from the external parties, who are not directly employed in the firm such as other supporting institutes, relatives and friends. This study adapts the mixed-method technique which the researcher adapts the quantitative approach in the first phase, followed by the qualitative approach in the second phase. The interpretation of the findings was done in the final phase. By integrating both quantitative and qualitative methods, this study allows the researcher to provide rich, deep and comprehensive explanations to address the research questions. The study in done in the state of Selangor and stratified random sampling was adapted. Questionnaires and semi structured in-depth interviews were conducted as means of collecting data. Based on the total number of population of G1 to G3, the sample size is 368 respondents. Quantitative research revealed that personal competency has the highest effect on the success of the construction firms (β=.231), and social network (β=.223). Moreover, themes emerged from in depth interviews are personal, strategic management, learning, opportunity, social network and inter-organization network. Small sized construction firms therefore must combine its individuals' entrepreneurial competencies and network competency in order to achieve competitive advantage. This competitive advantage acts as an impetus to the growth of small sized firms. Hence, the study's empirical findings provide a basis for recommendations for small size construction firms to enhance their competencies and for the policy makers to design and formulate entrepreneurship support programs and other initiative for SMEs especially the small size construction firms.